THE EFFECTIVENESS OF USING JOLLY PHONICS BLENDING PHONEMES TO YEAR 3 ENGLISH LANGUAGE CLASSROOM - Zulkifli Ahmad; Melor Md Yunus (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Poor word identifying skill has become an issue among weak students in the education system. Students with good skill of able to identifying words at glance are able to develop and improve their overall reading performance across subjects in the school compared to the weak students who has poor word identifying skill. This problem has not only brought a temporary halt to teachers to teach but also to students to understand any information or tasks transmitted through the teaching and learning process. In the process of word identifying skill, students must be able to recognize the sounds of letters which are phonemes that form a word. For that reason, the purpose of this study is to evaluate the effectiveness of using Jolly Phonics Blending Phonemes to 30 pupils of the Year 3 EL learners. This study uses the mix-mode method that uses the quantitative and qualitative research method to analysed the effect of the Jolly Phonics Blending Phonemes to the experimental group and the control group in the same school in six months. The findings have discovered that the experimental group had showed an overall increase in scores and interest towards the phonics teaching compared the control group that uses the traditional method of teaching phonics. The introduction of Jolly Phonics Blending Phonemes does affect the performance among the poor learners in the Year 3 EL classroom.